Rising Postoperative C-Reactive Protein in Congenital Diaphragmatic Hernia: Sepsis or Inflammation?. Issue 1 (March 2019) - Mukherjee, Devdeep; Ranganna, Ranganath
Abstract: This study aims to determine the incidence of sepsis in neonates operated for congenital diaphragmatic hernia and ascertain if the level or pattern of C-reactive protein (CRP) could be used to differentiate neonates with sepsis from noninfective inflammation. This study suggests that CRP patterns within the first 48-hours after surgical intervention for congenital diaphragmatic hernia could be used to differentiate neonates with noninfective inflammation from sepsis. A larger, multicentric study is needed to differentiate sepsis from inflammation on the basis of CRP rise and thereby help in avoiding unnecessary use of antibiotics.